Concept of Criminal Law on Corruption of Corporate Criminal Liability System Based on Justice Value - Abdul Kholiq; Gunarto Gunarto (Jurnal Daulat Hukum, 2021)
The purpose of writing is to analyze the corporate accountability system in order to impose crimes against corporations, and obstacles to imposing crimes against corporations. The method used is the statute approach and the case approach, the analysis method uses qualitative analysis with interpretation, and the data collection method uses library research. It can be concluded that corporations can be held accountable by using a system of absolute and substitute liability, and the obstacle is the application of a conventional criminal liability system and the difficulty of proving corporate wrongdoing. It is suggested that there is a common perception among law enforcers about the criminality of corporations.